ANALISA PERBANDINGAN BEBAN TRAFFIC FTP DALAM SISTEM MANET (MOBILE AD-HOC NETWORK) PADA PERGERAKAN MANHATTAN GRID DENGAN MENGGUNAKAN ROUTING PROTOKOL AODV DAN OLSR - Karisma Wiguna, I Made; Djuni, IGAK; Sudiarta, P.K. (Jurnal SPEKTRUM, 2019)
Advances in network technology have encouraged the development of ad-hoc services. MANET is one of them. In MANET, a routing protocol is required that can facilitate communication reliably. To get this reliable routing, in this study simulation of two routing protocols, namely AODV and OLSR. In the Manhattan Grid Mobility (MGM) model with communication loads using the FTP protocol. The simulation results show that the end-to-end value of service quality is 0.00210 second and throughput of 0.353428 Mbps for high FTP load in AODV routing. While the OLSR protocol routing obtained end to end delay value is 0.00071 second and throughput of 0.532025 Mbps for high load load FTP. For high load FTP traffic loads, 0.042436 second response time upload and 0.085789 second time response download on AODV protocol routing. On the OLSR routing protocol the upload time response rate is 0.084756 second response time and 0.09271 seconds download time response.